Pengaruh Persepsi Manfaat dan Kemudahan Penggunaan terhadap Minat Menggunakan Layanan Grab Food (Studi di Kota Kendari) - Jaya Saputra, Yusuf; Sumiyadi; Satyadharma, Maudhy (Program Studi Manajemen, Fakultas Ekonomi, Universitas Islam Majapahit, Jawa Timur, Indonesia, 2024)
Technological advances felt by society also have an impact on changes in the transportation sector with the presence of online transportation. With the increasing development of people's behavior, there are additional services available for online transportation, namely online food delivery services. Grabfood is one of the delivery services that is popular with the public, including in Kendari City as the capital of Southeast Sulawesi Province. This research aims to test and analyze the influence of perceived usefulness and perceived ease of use, both partially and simultaneously, on interest in using Grab Food services in Kendari City. This research uses quantitative descriptive methods. Data collection techniques in this research used questionnaires, observation and literature. The sample in this research was Kendari City residents who used the Grab Food service and were willing to fill out the questionnaire and numbered 120 people. The research results concluded that partially and simultaneously perceived usefulness and perceived ease of use had a positive and significant effect on interest in using Grab Food services in Kendari City.